Nature of the crust beneath the islands of the Mozambique Channel: Constraints from receiver functions. (December 2021) - Dofal, A.; Fontaine, F.R.; Michon, L.; Barruol, G.; Tkalčić, H.
Abstract: Starting in May 2018, a volcano-tectonic crisis occurred in the vicinity of Mayotte, a volcanic island in the Comoros Archipelago in the Mozambique Channel. The origin of the volcanism but also the subsurface architecture and nature of the crust, remain unknown. Here, based on receiver function analyses that provide S -wave velocity profiles, we determine the depth of Mohorovičić discontinuity ( Moho ) and V P /V S ratios for volcanic islands in the Mozambique Channel. We propose that the crust beneath Mayotte and Juan de Nova islands is of continental nature, while it appears to be of oceanic origin beneath Europa and Grande Glorieuse islands. Our results suggest that Mayotte edifice grew on an isolated continental block abandoned during the Gondwana breakup and the opening of the Mozambique Channel. The continental crust is underlain by a thick (9–10 km) and fast layer, interpreted as magmatic underplating which may result from the 20-Myr-long duration of the volcanism. The new velocity model determined from the seismic station on Mayotte can be used to relocate the seismicity related to the ongoing volcano-tectonic crisis. Highlights: We use receiver functions to image the crustal structure in the Mozambique Channel Mayotte Island is built on an underplated isolated continental block Thick underplating developed below the edifices of the MC due to a long activity Our velocity model help relocate the seismicity of the volcanic crisis of Mayotte